Cost analysis of parcel fragmentation in agriculture: The case of traditional olive cultivation. (December 2017) - Perujo Villanueva, Manuel; Colombo, Sergio
Abstract : Land fragmentation and dispersion hampers the optimisation of agricultural management. In this study, a methodology is proposed to quantify the extra costs to farmers caused by the spatial dispersion among agricultural parcels in their farms. The methodology proposed measures the length of the trips between parcels in the same farm, adds the inoperative periods due to the travel and then estimates the additional costs for fuel and labour. The study focuses on traditional olive cultivation in the province of Jaen, Spain, as a major crop with a highly fragmented and scattered structure. Thus, the profitability of this crop is seriously reduced so lower production costs become necessary to prevent crop abandonment. The results indicate that the dispersion of the olive parcels has a significant impact on production costs, with cases in which the expense of travel between parcels represents more than a quarter of the overall farming costs. The significant impact of the spatial dispersion of the parcels on production costs evidences the need for policies either to enlarge farm size or to encourage shared cultivation to offset the spatial scattering of olive parcels. Highlights: The majority of traditional olive farms are small and geographically dispersed. A new methodology is proposed to measure parcels dispersion and production costs. The costs of parcels dispersion are significant for small agricultural holdings. Farmers' cooperation can increase small agricultural holdings income.